Relação estrutura-propriedades-processamento de aços inoxidáveis martensíticos - Cláudio Moreira de Alcântara (2021)
AISI 420 martensitic stainless steel is widely used in the cutlery industry due to its high hardness, wear resistance and excellent corrosion resistance, properties acquired when this steel is subjected to heat treatment processes of quenching and tempering. However, when variables such as austenitizing temperature, soaking time and cooling speed are performed empirically or in an uncontrolled manner, this results in end product performance problems. The overall objective of this work was to study the effect of different austenitization and tempering temperatures on the microstructure, mechanical properties, impact and corrosion resistance. For this, two martensitic stainless steels AISI 420 produced by the company Aperam South America were chosen, whose difference between the two materials is in the carbon content, where the steel known internally as P420D has a carbon content in the order of 0.18% and the P420A steel has a carbon content of 0.32%. The tests were carried out through laboratory-scale quenching and tempering heat treatments at four different temperatures. The samples were characterized through metallographic, hardness, mechanical and impact strength tests. P420A steel had higher hardness values than P420D steel, where its higher carbon content influenced this variable in different treatment conditions. P420A steel has higher mechanical property values than P420D steel due to the higher carbon content of this alloy, however both steels' yield and strength limit properties increase as the austenitization temperature increases. The Steels show improved mechanical property values when subjected to different tempering temperatures. P420A and P420D steels have low impact energy values when as quenched, however P420D steel has a significant improvement in this property when subjected to tempering temperatures. Corrosion resistance improves with increasing austenitization temperature, but 420D steel has better pitting resistance values due to its lower carbon content than P420A steel.